Penggunaan Zat Aditif Graphene Pada Campuran Asphalt Concrete- Wearing Course (AC-WC) - Syukri Hamdani; Muhammad Shalahuddin; Yosi Alwinda; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
One type of road pavement layers that susceptible to damage is Asphalt Concrete-Wearing Course (AC-WC). AC-WC is the top layer of the road pavement structure. One effort that can be carried out to improve the quality of asphalt pavement is to modify the asphalt mixture materials by using additive. Graphene is one of the materials that can be used as asphalt additive. Several previous studies have used this material in various reinforcement structures. The aim of this study was to determine the effect of using asphalt that has been mixed with graphene as the additive in the AC-WC mixture based on the value of Marshall characteristics. Variations made in this study were 0% (without mixture) as a comparison, 0.5%, 1%, and 1.5% of asphalt weight. This research was carried out by designing the AC-WC mixture based on the gradation specifications of combined aggregate for each variation. The specimens of Marshall test were made for each variation. Graphene was made by using the Electrochemical and Mechanical Liquid Exfoliation (EMLE) method. The results showed that the use of graphene as the additive in the AC-WC mixture affected the value of Marshall characteristics. The best value that meets the general specifications of Bina Marga 2010 revision 3 was obtained in the addition of 1.5% graphene, with stability value 1485 kg or an increase of 28.57%, flow value 4.25 mm, VIM value 6%, VMA value 18.3%, VFA value 65%, and MQ value 345 kg/mm.Keywords: Graphene, Additives, AC-WC, General Specifications of Bina Marga 2010 Revision 3, Marshall